EFEK AKTIVITAS MASYARAKAT TERHADAP KEBERADAAN IKAN CENCEN (Mystacoleucus marginatus) DI SUNGAI SIBIRU-BIRU KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA - Charo Lina Kaban; Hesti Wahyuningsih; Desrita Desrita (AQUACOASTMARINE, 2016)
Utilization of the river as a waste water disposal is the impact of community activities that can cause environmental changes that would be bad for the life aquatic organisms. The changing quality of the waters is affecting the lives of organisms, including fish. The existence cencen fish (Mystacoleucus marginatus) in the waters is largely determined by the physical and chemical conditions of the waters. The aim of this research is to analyze the density of cencen fish and water quality. This research was on April-June 2015 in Sibiru-Biru river. Samples were taken from four observation stations and at each station observations performed 3 repetitions. In order to determination sample location is using “Purposive Sampling” and sample analyzed water quality. The result of research in Sibiru-Biru river have been found one class from ordo Cypriniformes is for about 92. The highest population fishes density Cencen fish with grade 0,45 individuals/m2. Meanwhile the lowest population fish density Cencen fish is about 0,08 individuals/m2. The water quality of Sibiru-Biru River was polluted category. Based on the relationship expressed heavy growth patterns of Cencen fish in Sibiru-Biru river growth months are negatively allometric, meaning that the growth of fish length cencen more dominant than the growth in weight.Key words : Density, Pollution Levels, and Growth.